Pengaruh Digital Marketing Dan Digital Payment Terhadap Minat Beli Konsumen Janji Jiwa Arif Rahman Cianjur - Nuraida, Widy; Apriadi, Deri (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The purpose of this research is to study how the use of online promotion strategies through Instagram impacts customer interest in the Janji Jiwa Arif Rahman Cianjur outlet. This research was conducted through a quantitative approach, and data was collected through questionnaires that can be accessed online. The number of respondents in this study were forty people who had purchased the coffee shop's products. The data obtained was then analyzed through multiple linear regression analysis and hypothesis testing using the F test and t test. The results showed that the Digital Marketing variable had the greatest influence on customer interest in the outlet. These variables affect customer interest both overall and partially. Therefore, companies need to maximize the use of Digital Marketing by providing details about promos, discounts and other innovations by following trends, working with influencers or endorsements, and consistently creating creative content to reach a larger audience.